2015
DOI: 10.1097/md.0000000000001092
|View full text |Cite|
|
Sign up to set email alerts
|

Low Discrepancy Between Tissue Biopsy Plus Magnifying Endoscopy With Narrow-Band Imaging and Endoscopic Resection in the Diagnosis of Gastric Epithelial Neoplasia (STROBE)

Abstract: Tissue biopsy is often not very accurate for the diagnosis of gastric epithelial neoplasia (GEN), and the results differ notably from endoscopic resection (ER) in terms of the pathological diagnosis. The aims of this study were to evaluate the diagnostic performances of biopsy, magnifying endoscopy with narrow-band imaging (ME-NBI), and biopsy plus ME-NBI for GEN.This study retrospectively analyzed 101 cases diagnosed as GEN using ER samples. The discrepancies between biopsy and ER, as well as between biopsy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…First, GC is a heterogeneous disease and biopsy specimens may not be considered to be representative of the entire lesion. Although increasing the number of biopsy specimens may decrease the discordance rate between biopsy and resection specimens, multiple biopsies may cause ulceration and submucosal fibrosis, which increase the risks related to endoscopic resection, such as bleeding and perforation . Second, the differential diagnosis between LGD and regenerative lesions is sometimes difficult, which may lead to the overuse of LGD diagnosis by pathologists .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, GC is a heterogeneous disease and biopsy specimens may not be considered to be representative of the entire lesion. Although increasing the number of biopsy specimens may decrease the discordance rate between biopsy and resection specimens, multiple biopsies may cause ulceration and submucosal fibrosis, which increase the risks related to endoscopic resection, such as bleeding and perforation . Second, the differential diagnosis between LGD and regenerative lesions is sometimes difficult, which may lead to the overuse of LGD diagnosis by pathologists .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ME‐NBI has high accuracy in distinguishing between gastritis and cancer. Biopsy combined with ME‐NBI can improve diagnostic consistency with the pathological results of endoscopically resected specimens . Hwang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Not an endoscopic screening study. Zhang et al, 2015 50 Not an endoscopic screening study. Shichijo et al, 2015 51 Not an endoscopic screening study.…”
mentioning
confidence: 99%
“…[18,19] A study also reported that more than 80% of HGINs progress to adenocarcinomas. [20] In our study, 54 patients (30%) showed adenocarcinomas under ESD while HGINs under CFB.…”
Section: Discussionmentioning
confidence: 99%